2011
DOI: 10.1007/s13258-011-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

The THO complex is required for stress tolerance and longevity in Drosophila

Abstract: The THO complex is an evolutionary conserved multi-subunit protein complex. Although its role in the formation of exportcompetent messenger ribonucleoproteins (mRNPs) is well established at the single cell level, it is still largely unknown about its specific roles at the multi-cellular organism level.Here we show that Drosophila THO complex is required for normal life span and environmental stress response. Mutant flies defective in the THO complex showed increased susceptibility to certain environmental stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…It has been well established that PI3K/AKT signaling pathway is a key player in regulating life span as well as body size in Drosophila (Edgar, 2006). Combined with the previously reported lifespan reduction (Kim et al, 2011), increased body size in the THO mutant flies compared to control is well matched with the known phenotypes of mutant flies with defects in PI3K/AKT signaling pathway (Edgar, 2006). Although we failed to detect a global increase in PI3K/AKT signaling in the THO mutant flies (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…It has been well established that PI3K/AKT signaling pathway is a key player in regulating life span as well as body size in Drosophila (Edgar, 2006). Combined with the previously reported lifespan reduction (Kim et al, 2011), increased body size in the THO mutant flies compared to control is well matched with the known phenotypes of mutant flies with defects in PI3K/AKT signaling pathway (Edgar, 2006). Although we failed to detect a global increase in PI3K/AKT signaling in the THO mutant flies (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 78%
“…In the previous report, we showed the reduced life span and the increased susceptibility to the environmental stresses in mutant flies for Drosophila THO subunits (Kim et al, 2011). To understand the underlying mechanisms of these defects, here we investigated genetic interactions of THO with 2 cellular signaling pathways, p53 and PI3K/AKT pathways.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…and Y.D.C., unpublished). Our recent work also showed that longevity and tolerance to environmental stress were significantly reduced in the THO mutants (Kim et al, 2011). This suggests that the role of the THO complex is not limited to spermatogenesis, but is also important for other types of cells.…”
Section: Research Articlementioning
confidence: 68%
“…Primary antibodies used in this study were: anti-THOC7 (Kim et al, 2011) at 1:1000, anti-HPR1 (Rehwinkel et al, 2004) at 1:100, anti-THO2 (Rehwinkel et al, 2004) at 1:100, anti-THOC5 (Kopytova et al, 2010) at 1:100 and anti-Fibrillarin (38F3; Santa Cruz, sc-56676) at 1:50. The secondary antibodies Alexa 546-conjugated goat anti-rabbit (1:500) and Alexa 488-conjugated goat anti-mouse (1:500) were purchased from Molecular Probes.…”
Section: Antibody Staining and Microscopymentioning
confidence: 99%